Mcl-1 and Bok transmembrane domains: unexpected players in the modulation of apoptosis - Lucendo, Estefanía; Lolicato, Fabio (Proceedings of the National Academy of Sciences of the United States of America, 2020)
The Bcl-2 protein family comprises both pro- and antiapoptotic members that control the permeabilization of the mitochondrial outer membrane, a crucial step in the modulation of apoptosis. Recent research has demonstrated that the carboxyl-terminal transmembrane domain (TMD) of some Bcl-2 protein family members can modulate apoptosis; however, the transmembrane interactome of the antiapoptotic protein Mcl-1 remains largely unexplored. Here, we demonstrate that the Mcl-1 TMD forms homooligomers in the mitochondrial membrane, competes with full-length Mcl-1 protein with regards to its antiapoptotic function, and induces cell death in a Bok-dependent manner. While the Bok TMD oligomers locate preferentially to the endoplasmic reticulum (ER), heterooligomerization between the TMDs of Mcl-1 and Bok predominantly takes place at the mitochondrial membrane. Strikingly, the coexpression of Mcl-1 and Bok TMDs produces an increase in ER mitochondrial-associated membranes, suggesting an active role of Mcl-1 in the induced mitochondrial targeting of Bok. Finally, the introduction of Mcl-1 TMD somatic mutations detected in cancer patients alters the TMD interaction pattern to provide the Mcl-1 protein with enhanced antiapoptotic activity, thereby highlighting the clinical relevance of Mcl-1 TMD interactions.